Systematic Literature Review: Computational Thinking Through Unplugged Activities Based On Spatial Reasoning Maps - Ulwan, Muhammad Nasheh; Supriatna, Encep; Bait, Elmi Hanjar (International Conference on Elementary Education, 2025)
Computational thinking (CT) has been recognized as a fundamental 21st-century literacy, yet its integration into the elementary curriculum remains constrained by limited technological resources. This systematic literature review synthesizes research evidence on map-based unplugged activities for fostering CT skills, proposing a novel framework positioning spatial reasoning as the cognitive catalyst. Following PRISMA guidelines, this review examined peer-reviewed studies from multiple international databases, applying predefined inclusion criteria aligned with elementary education contexts. Findings demonstrate strong alignment between cartographic practices, spatial reasoning, and CT components, particularly through activities such as map-making and grid navigation. However, challenges persist in transferring unplugged CT skills into digital contexts. To address this gap, the Up-SpCT Pedagogical Model is introduced as a structured developmental pathway bridging spatially grounded unplugged experiences and digital CT engagement. This review highlights that map-based unplugged activities can be effectively integrated into elementary classrooms to build computational thinking foundations. The findings provide practical guidance for teachers to design spatially grounded unplugged lessons and inform curriculum developers on integrating CT as a transversal competency in primary education.